PENGARUH KONSENTRASI PENSTABIL DAN SUKROSA TERHADAP KARAKTERISTIK SARI BONGGOL NANAS (Ananas comosus l. merr) INSTAN DENGAN METODE KOKRISTALISASI - ina siti nurminabari (Department of Food Technology, Universitas Pasundan, Bandung, 2019)
Pineapple is one of the fruit plants that has long been widely known by the public. Pineapple is not native to Indonesia, this plant comes from the American continent. The purpose of this study was to study the effect of CMC stabilizer and sucrose concentration on the characteristics of instant pineapple cork extract (Ananas comosus L. merr) with the cocrystallization method. The benefit of this research is to add insight to the research, add and develop science and technology regarding pineapple hump juice as food preparations, and to lift local raw materials that have not been utilized so that they have added value and increase the use value and economic value of pineapple corm. The experimental design method used in the study of cocrystallization of pineapple hump juice was a 3 x 3 factorial experimental design in a randomized block design (RBD), carried out 3 (three) times repetition, to obtain 27 experimental units. The experiment variable consisted of CMC (p) and sucrose (s) stabilizer concentration. The response in this study is the chemical response, namely reducing sugar content, crude fiber content, vitamin C content, water content. Physical response is soluble time. Organoleptic responses include aroma, color, and taste. The results showed that the levels of vitamin C extract of pineapple extract in the introduction were 55.73 mg / 100 grams, the reduction level of pineapple cusp extract was 18.92%, and the crude fiber content of pineapple cusp extract was 0.953%. The results of the main research testing that the concentration of CMC stabilizer and sucrose affect the water content, soluble time, organoleptic response, namely color, and aroma. The interaction between stabilizer and sucrose concentrations influences the water content, when soluble the organoleptic response to color, and Rome.